Implementation of Online Learning Policy - Afdaliah Rauf; Sangkala; Hasniati (IHSA Institute, 2022)
This study uses a qualitative descriptive method that is focused on clearly seeing how the implementation of online learning policies at the State Junior High School 3 Barru are also obstacles and opportunities in learning activities during the Covid-19 period. The results showed that the implementation of online learning at the State Junior High School 3 Barru can run well, although not optimally. opportunities and obstacles in online learning, namely the internet network, speed, flexibility, quota, signal, place of residence and so on, all of which have an influence on learning activities